Erythrocytic nuclear abnormalities and leucocyte profiles of Asian seabass (Lates calcarifer) exposed to polluted seawater - Sinlapachai Senarat; Anek Sopon; Jes Kettratad; Kitipong Angsujinda; Natthawut Charoenphon; Pahol Kosiyachinda; Kitiya Kongthong; Pisit Poolprasert; Piyakorn Boonyoung; Piyamat Kongtueng (Universiti Kebangsaan Malaysia, 2023)
Close to industrial activity and a major seaport in the Gulf of Thailand, Sichang Island has frequently suffered from pollution and oil spills. However, the environmental health status of the surrounding waters is relatively unknown. Between December 2017 and January 2018, we reared ninety Asian seabass (Lates calcarifer) in cage nets off the island and sampled blood to investigate nuclear abnormalities in erythrocytes and build leucocyte profiles. The fish were purchased locally and reared in locations where oil spills have been recorded. Environmental parameters were within the range of standard values. Erythrocyte nuclei had segmented, reniform and notched abnormalities; however, they dramatically varied after exposure. At the end of the three-month field experiment, very few micronuclei had been observed. Observed leucocytes were neutrophils, lymphocytes, and monocytes. The percentage of lymphocytes increased considerably, reaching a post-exposure peak at three months. Our data suggest that erythrocytic nuclear abnormalities of Asian seabass could be used as an early warning of toxic pollutants in the marine environment, and as a baseline environmental health indicator for Sichang Island and the surrounding area.